Decreased plasma levels of activated factor VII in patients with deep vein thrombosis. (22nd May 2015) - Schut, A. M.; Meijers, J. C. M.; Lisman‐ van Leeuwen, Y.; van Montfoort, M. L.; Roest, M.; de Groot, P. G.; Urbanus, R. T.; Coppens, M.; Lisman, T.
Summary Background The initiating trigger in the development of deep vein thrombosis (DVT) remains unidentified. It has been suggested that tissue factor (TF)‐bearing microparticles play a key role, which indicates a role for the TF pathway in the initiation of DVT. Objective To assess the role of the TF pathway in the initiation of venous thrombosis, we measured plasma levels of factor VII and VIIa in patients with acute DVT and in controls. Methods We included 148 patients diagnosed with acute DVT and 179 controls in this study. Antigen levels of FVII and FVIIa were measured by using assays recently developed in our laboratory. Results Median FVII levels in patients were 109.8% (interquartile range [IQR] 86.0–153.2) compared with 102.2% (IQR 76.1–141.7) in controls. Individuals with FVII levels in the upper quartile had a 1.6–fold increased risk for the presence of a DVT (odds ratio 1.6, 95% confidence interval 0.8–3.1). Median FVIIa levels in patients were 50.2 ng mL−1 (IQR 25.2–86.1) compared with 96.6 ng mL−1 (69.9–168.9) in controls. Individuals with FVIIa levels in the lowest quartile had a > 5‐fold increased risk for the presence of a DVT (odds ratio 5.5, 95% confidence interval 2.8–10.6). Both risks did not change substantially after adjustment for potential confounders. Conclusion Decreased plasma levels of FVIIa in patients with deep vein thrombosis may indicate ongoing consumption of FVIIa and suggest a contributory role for TF in venous thrombus formation.